2014
DOI: 10.1016/j.bbrc.2014.06.130
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazoles diminish ERE transcriptional activity and cell growth in breast cancer cells

Abstract: Estrogen receptors (ERα and ERβ) are members of the nuclear receptor superfamily. They regulate the transcription of estrogen-responsive genes and mediate numerous estrogen related diseases (i.e., fertility, osteoporosis, cancer, etc.). As such, ERs are potentially useful targets for developing therapies and diagnostic tools for hormonally responsive human breast cancers. In this work, two benzimidazole-based sulphonamides originally designed to reduce proliferation in prostate cancer, have been evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…3,19 Methyl or naphthyl attached benzimidazole structures also demonstrate SERMlike actions on breast cancer cell lines. 3,[19][20][21] In line with the above-mentioned findings, we have previously identified several ethylsulfonyl indole-benzimidazole derivatives with antiestrogenic properties. 22 Interestingly, antiproliferative effects were distinct based on ER status where ERa-positive cell lines MCF-7 and HEPG2 resulted in overlapping cell viability profiles across various compound concentrations in comparison with ERa-negative cell line MDA-MB-231.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…3,19 Methyl or naphthyl attached benzimidazole structures also demonstrate SERMlike actions on breast cancer cell lines. 3,[19][20][21] In line with the above-mentioned findings, we have previously identified several ethylsulfonyl indole-benzimidazole derivatives with antiestrogenic properties. 22 Interestingly, antiproliferative effects were distinct based on ER status where ERa-positive cell lines MCF-7 and HEPG2 resulted in overlapping cell viability profiles across various compound concentrations in comparison with ERa-negative cell line MDA-MB-231.…”
Section: Introductionmentioning
confidence: 62%
“…In addition to the widely used first generation SERM known as tamoxifen, 11,12 there are other second and third generation SERMs developed to reduce side effects associated with tamoxifen. 11,13 For instance, the affinity of third generation bazedoxifene is more selective towards the ERa rather than ERb, hence its inhibitory effect progresses through ERa downregulation and cell cycle arrest. 11 In addition, bazedoxifene with palbociclib combination is a promising therapeutic option in clinics, and tested against metastatic BC at stage IV.…”
Section: Introductionmentioning
confidence: 99%
“…A quick look at the literature shows several works on derivatives of BZM, BTA, and BOX, especially those substituted at the 2 position, which have shown important biological activity against different types of neoplasms, including breast cancer [ 36 , 37 , 38 , 39 , 40 ]. It has been pointed out that the mechanisms of action of these benzo [ d ] [1,3] azole are different, highlighting in an important way the signaling pathways modulated by ERs [ 41 , 42 , 43 , 44 ]. Thus, following our continuous interest in the synthesis of benzofused heterocyclic derivatives and the study of their potential biological activities, in this opportunity, we report here the synthesis and characterization of a series of benzo [ d ] [1,3] azoles substituted at position 2 with benzyl and allyl-sulfanyl groups ( BTA-1 , BZM-2 , BOX-3 , BTA-4 , BZM-5 and BOX-6 ) and their preliminary in vitro cytotoxic assays against different human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…
Benzimidazoles have generated a great deal of interest because of their important roles in organic synthesis and the pharmaceutical industry. [1][2][3][4][5][6][7] The benzimidazole system can be found in some medicinal compounds such as omeprazole, thiabendazole and albendazole. [8][9][10][11][12] Recently, it was reported that some benzimidazoles derivatives containing fluorine atom and 1-piperazinyl moiety have a valuable biological activity.
…”
mentioning
confidence: 99%
“…The iminoester hydrochlorides were synthesised according to the Pinner method. 24 Then, these compounds were reacted with compound 2 to synthesise the corresponding benzimidazole derivatives (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).The synthesis of 4-fluoro-5-(4-phenylpiperazin-1-yl) benzene-1,2-diamine (2) was performed under microwave irradiation in ethanol by using Pd/C (10%) catalyst and hydrazine monohydrate. Using this method, the compound was easily synthesised in good yield without the need for further purification before the next step.…”
mentioning
confidence: 99%